Cellulose nanofiber-layered double hydroxide composite material as well as preparation method and application thereof
By mixing the cellulose nano -fiber and layer -like hydrogen oxide in the solution, and using one -way frozen technology to prepare a composite material with an orderly orientation structure, it solves the problem that the existing material is difficult to meet the spinal cord damage repair bridge structure. The effective application of composite materials in spinal cord injury repair has promoted nerve regeneration and motion function recovery.
Patent Information
- Application Number
- CN202411294117.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-24
AI Technical Summary
The existing layered double hydroxide materials are difficult to meet the bridge structure required for spinal cord injury repair, which limits its research and development in the field of spinal cord injury repair.
By mixing the cellulose nano -fiber and layer -like hydrogen oxides in the solution, the unidirectional frozen technology is used to prepare a composite material with an orderly orientation pore structure, and further loads the small molecular drug RA and the neurnutic nutritional factor SHH to obtain functionalization. Composite materials.
The effective application of composite materials in spinal cord injury repair was realized, promoting the proliferation and differentiation of neural stem cells, promoting axon regeneration and neural circuit reconstruction, and significantly restoring the motor function of mice with spinal cord injury.
Smart Images

Figure CN119345477A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a cellulose nanofiber-layered double hydroxide composite material, a preparation method thereof, and applications thereof. Background Art
[0002] Spinal cord injury can lead to axonal severance and the death of numerous neurons and oligodendrocytes. Furthermore, the limited regenerative capacity of spinal cord tissue after injury, along with the inflammatory microenvironment and glial scar formation, complicate nerve regeneration and remodeling of the conduction circuit. Bioscaffolds can mimic the effects of the extracellular matrix to promote endogenous nerve regeneration. Their unique microstructure can also induce axonal extension, achieving superior injury repair outcomes.
[0003] Currently, a variety of biomaterials are used to construct bioscaffolds for repairing spinal cord injuries. Among them, layered double hydroxide (LDH) is a biodegradable nanomaterial with the characteristics of good biocompatibility, biodegradability, sustained / controlled drug release, and targeted transport. It has been proven to effectively regulate the inflammatory microenvironment of the injured area, promote the migration and differentiation of neural stem cells (NSC), and make nerve regeneration and neural circuit reconstruction at the site of spinal cord injury possible. However, simple layered double hydroxide cannot well meet the bridge structure required for spinal cord injury repair, which greatly limits its research and development in the field of spinal cord injury repair.
[0004] Cellulose nanofibers (CNFs) have a high aspect ratio and good biocompatibility, allowing them to construct ECM-like network structures. Composite bioscaffolds prepared using cellulose as a matrix material have been used as various stem cell culture platforms, such as maintaining the multipotency of human adipose-derived stem cells, regulating the chondrogenic differentiation of mouse bone marrow mesenchymal stem cells, and directing the differentiation of neural stem cells into neuronal lineages. However, research on cellulose nanofiber-based bioscaffolds for repairing spinal cord injuries is currently limited, and further investigation of their repair effects and mechanisms is needed to lay a theoretical and experimental foundation for the subsequent clinical application of cellulose nanofiber-based bioscaffolds. Summary of the Invention
[0005] To address these technical issues, the present invention provides a cellulose nanofiber-layered double hydroxide composite material, its preparation method, and its application. The composite material provided by the present invention has an ordered, guided pore structure for sustained factor release, and has potential applications in regulating cell fate and repairing spinal cord injuries.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In one aspect, the present invention provides a method for preparing a cellulose nanofiber-layered double hydroxide composite material, comprising the following steps:
[0008] Layered double hydroxide (LDH) and cellulose nanofiber (CNF) are uniformly mixed in a solution, and then subjected to ① drying or ② unidirectional freezing to obtain the cellulose nanofiber-layered double hydroxide composite material.
[0009] As a preferred embodiment, the layered double hydroxide is magnesium iron layered double hydroxide (MgFe-LDH);
[0010] Preferably, the mass ratio of the cellulose nanofibers to the layered double hydroxide is 10 to 40:1.
[0011] As a preferred embodiment, the preparation method of the magnesium / iron layered double hydroxide comprises the following steps:
[0012] S1. Add the mixed solution of magnesium nitrate and ferric nitrate to the NaOH solution and stir at 25-60°C for 30-60 minutes;
[0013] S2. The product of step S1 is subjected to a hydrothermal reaction at 80 to 120 ° C for 14 to 18 hours to obtain a magnesium / iron layered double hydroxide;
[0014] Preferably, the molar ratio of magnesium to iron in the magnesium nitrate and ferric nitrate is (0.1-5):1;
[0015] Preferably, after the mixed solution of magnesium nitrate and ferric nitrate is added to the NaOH solution, the final molar concentration ratio of magnesium nitrate to sodium hydroxide is (0.375-1.2):1;
[0016] Preferably, the solvent of the mixed solution of magnesium nitrate and ferric nitrate is CO2-free deionized water;
[0017] Preferably, the solvent of the NaOH solution is CO2-free deionized water;
[0018] Preferably, the stirring reaction in step S1 is carried out under continuous nitrogen flow.
[0019] As a preferred embodiment, the drying is vacuum drying;
[0020] Preferably, the drying temperature is 40-80°C.
[0021] As a preferred embodiment, the unidirectional freezing is to introduce the uniformly mixed solution into a mold with one side made of metal and the other side made of non-heat-conducting material for unidirectional freezing. In the technical solution of the present invention, during the unidirectional freezing process, the mixed solution exchanges heat with the outside world on the metal surface, causing ice crystals to gradually grow upward in a unidirectional direction.
[0022] Preferably, the temperature of the one-way freezing is -80 to -196°C;
[0023] Preferably, the thermal conductivity of the metal is ≥400 W / (m*K), such as copper, silver, etc.;
[0024] Preferably, the one-way freezing time is 40 to 60 minutes;
[0025] In certain specific embodiments, the unidirectional freezing is performed in liquid nitrogen;
[0026] In certain specific embodiments, the liquid height of the uniformly mixed solution in the mold is 2 / 5 to 4 / 5 of the height of the mold;
[0027] In certain specific embodiments, the mold is a centrifuge tube with a tube body wrapped by a heat insulating material and a tube opening covered by metal;
[0028] In certain specific embodiments, the uniformly mixed solution is subjected to a centrifugal operation to remove bubbles before the one-way freezing;
[0029] In certain specific embodiments, the specific operation of the unidirectional freezing is to pour 20 to 40 mL of the evenly mixed solution into a 50 mL centrifuge tube and centrifuge at 1000 to 1200 rpm to remove bubbles; wrap the centrifuge tube with 1 to 2 cm thick foam plastic, place the mouth of the centrifuge tube upside down on a copper block at -80 to -196°C, and perform unidirectional freezing for 40 to 60 minutes, so that ice crystals gradually grow upward in a unidirectional direction.
[0030] As a preferred embodiment, the one-way freezing further includes freeze drying;
[0031] Preferably, the freeze-drying temperature is -80 to 85°C.
[0032] In another aspect, the present invention provides a cellulose nanofiber-layered double hydroxide composite material obtained by the above preparation method. In the technical solution of the present invention, the cellulose nanofiber-layered double hydroxide composite material obtained by the above preparation method has an ordered micron-scale guided pore structure.
[0033] In another aspect, the present invention provides a method for preparing a functionalized cellulose nanofiber-layered double hydroxide composite material, comprising the following steps:
[0034] The cellulose nanofiber-layered double hydroxide composite material is treated under ultraviolet light, immersed in a mixed solution containing sonic hedgehog (SHH) and vitamin A acid (RA), and freeze-dried to obtain the functionalized cellulose nanofiber-layered double hydroxide composite material.
[0035] As a preferred embodiment, the ultraviolet treatment time is 16 to 24 hours;
[0036] Preferably, the ratio of the mass of the cellulose nanofiber-layered double hydroxide composite material to the total mass of sonic hedgehog (SHH) and retinoic acid (RA) is 10 to 1000:1;
[0037] Preferably, the mass ratio of retinoic acid (RA) to sonic hedgehog (SHH) is 1 to 20:10;
[0038] Preferably, the solvent in the mixed solution containing sonic hedgehog (SHH) and retinoic acid (RA) is a PBS buffer solution;
[0039] Preferably, the freeze-drying temperature is -80 to 85°C.
[0040] In another aspect, the present invention provides a functionalized cellulose nanofiber-layered double hydroxide composite material obtained by the above preparation method.
[0041] In another aspect, the present invention provides use of the above-mentioned preparation method, the above-mentioned cellulose nanofiber-layered double hydroxide composite material, or the above-mentioned functionalized cellulose nanofiber-layered double hydroxide composite material in preparing a biological scaffold.
[0042] In certain specific embodiments, the preparation of the bioscaffold comprises rehydrating the composite material obtained by the above preparation method, the above cellulose nanofiber-layered double hydroxide composite material, or the above functionalized cellulose nanofiber-layered double hydroxide composite material;
[0043] Preferably, the temperature of the rehydration operation is 4-8°C;
[0044] Preferably, the rehydration operation time is 1 to 12 hours.
[0045] As a preferred embodiment, the application is application in preparing a spinal cord injury repair scaffold.
[0046] The above technical solution has the following advantages or beneficial effects:
[0047] The cellulose nanofiber-layered double hydroxide composite material provided by the present invention utilizes a unidirectional freezing technique to create a complete, ordered micron-scale guided pore structure within the composite material. The cellulose nanofiber-layered double hydroxide composite material provided by the present invention can be further loaded with the small molecule drug RA and the neurotrophic factor SHH to obtain a functionalized cellulose nanofiber-layered double hydroxide composite material.
[0048] The composite materials and functionalized composite materials provided by the present invention have physicochemical properties that appropriately match those of the spinal cord and exhibit good biocompatibility. These composite materials can promote the proliferation of rat neural stem cells, regulate and direct the differentiation of neural stem cells toward neuronal and oligodendrocyte lineages, and inhibit differentiation toward astrocyte lineages. Furthermore, transplanting bioscaffolds prepared from these composite materials at the site of spinal cord injury can promote axonal regeneration and neural circuit connectivity in the injured area, significantly restoring motor function in mice with spinal cord injury. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a characterization test diagram of the MgFe-LDH synthesized in Example 1.1 of the present invention; wherein, Figure 1 A is the morphology of MgFe-LDH characterized by TEM; Figure 1 B is the characteristic diffraction peak pattern of MgFe-LDH detected by XRD.
[0050] Figure 2 This is a characterization test diagram of the CNF-LDH composite material with an ordered guided pore structure prepared in Example 1.3 of the present invention; wherein, Figure 2 A is a physical picture of CNF-LDH mixtures with different mass ratios and a cross-sectional view of a CNF-LDH composite material with a mass ratio of 20:1; Figure 2 B is the structure and related element distribution of CNF-LDH composite material characterized by SEM and EDS.
[0051] Figure 3 This is a diagram showing the cell compatibility test results of the CNF-LDH composite material in Example 2 of the present invention; wherein, Figure 3 A is the quantitative analysis result of cell activity after NSC and composite material were co-cultured for 48 hours; Figure 3 B and Figure 3 C is a cell proliferation analysis chart, where Figure 3 B is the statistical diagram of quantitative analysis of mean fluorescence intensity. Figure 3 C is the binding image of EdU and DNA observed under a fluorescence microscope.
[0052] Figure 4 This is a graph showing the expression levels of Tuj1, MAP2, GFAP, and Olig2 detected by RT-PCR in the CNF-LDH composite scaffold-induced NSC differentiation experiment in Example 3 of the present invention.
[0053] Figure 5 This is a graph showing the expression levels of Tuj1, MAP2, GFAP, and Olig2 detected by RT-qPCR in the NSC differentiation regulation experiment using a functionalized CNF-LDH-RS composite scaffold in Example 3 of the present invention.
[0054] FIG6 is a graph showing electrophysiological and motor recovery in mice in Example 4 of the present invention; wherein, Figure 6A These are imaging photos of mouse hind limb movements 8 weeks after surgery; Figure 6B Statistical analysis of BMS scores for each group of animals; Figure 6C -D is the quantitative analysis of MEP amplitude and latency in each group of animals 8 weeks after injury.
[0055] Figure 7 This is a detection diagram of neuron regeneration 3 and 6 weeks after transplantation in Example 4 of the present invention; wherein, Figure 7 A is immunostaining of Tuj1 (green) in spinal cord tissue sections of mice 3 weeks after injury; Figure 7 B is every 0.045 mm 3 weeks after injury 2 Statistical analysis of the area of Tuj1-positive cells in the damaged area; Figure 7 C is Tuj1 (green) immunostaining of spinal cord tissue sections of mice 6 weeks after injury; Figure 7 D is 0.045 mm every 6 weeks after injury 2 Statistical analysis of the area of Tuj1-positive cells in the damaged area; Figure 7 E is the statistical analysis of the length of regenerated axons in the injured area 3 and 6 weeks after injury.
[0056] Figure 8 These are representative images of immunostaining of MAP2 (green) and GFAP (red) in spinal cord tissue sections of mice in each group 8 weeks after transplantation in Example 4 of the present invention, as well as detection images of the corresponding magnified images of each group.
[0057] Figure 9 These are representative detection images of MAP2 (red) and GFP (green) positive neurons in each group of mice 8 weeks after transplantation in Example 4 of the present invention. DETAILED DESCRIPTION
[0058] The following embodiments are merely some of the embodiments of the present invention, rather than all of them. Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the claimed invention, but rather merely represents selected embodiments of the present invention. All other embodiments derived by those skilled in the art based on the embodiments of the present invention without creative effort are intended to fall within the scope of protection of the present invention.
[0059] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.
[0060] Example 1: Cellulose Nanofiber-Layered Double Hydroxide (CNF-LDH) Composite Material Example 1.1 Preparation of Magnesium Iron Layered Double Hydroxide (MgFe-LDH)
[0061] Dissolve 1.538 g of Mg(NO3)2·6H2O and 0.606 g of Fe(NO3)3·9H2O in 20 mL of CO2-free deionized water; dissolve 0.544 g of NaOH in 80 mL of CO2-free deionized water to prepare metal salt stock solutions and NaOH stock solutions;
[0062] In a three-necked round-bottom flask, nitrogen was introduced and the metal salt solution was added dropwise to the NaOH stock solution under vigorous stirring at 500 rpm. The reaction was carried out at 60°C for 30 min. During this process, nitrogen was continuously introduced to prevent carbonate contamination from the air.
[0063] The obtained precipitate was repeatedly washed with deionized water and centrifuged to remove impurities; the purified precipitate was dispersed in 100 mL of deionized water and hydrothermally treated at 100° C. in a stainless steel autoclave for 16 h; after the reaction, the precipitate was centrifuged and washed three times to obtain magnesium-iron layered double hydroxide nanoparticles.
[0064] The dispersion of the magnesium-iron layered double hydroxide nanoparticles with appropriate concentration was ultrasonically treated for 30 min, and the surface morphology was characterized by transmission electron microscopy (TEM). Figure 1 A: MgFe LDH nanoparticles have a hexagonal lamellar structure and a size of 70 to 125 nm.
[0065] The dispersion of the magnesium iron layered double hydroxide nanoparticles was freeze-dried, ground into powder using a mortar and pestle, and poured onto the center of a clean sample plate. After flattening, the diffraction pattern in the range of 10-80° was detected using an X-ray diffractometer (XRD) at an accelerating voltage of 40 kV and a current of 40 mA. The results were as follows: Figure 1 As shown in B: MgFe-LDH nanomaterials have obvious characteristic diffraction peaks (003), (006) and (009), and these diffraction peaks are sharp, symmetrical and narrow, indicating that the synthesized nanomaterials have orderly crystal surface growth, complete layered structure and good crystallinity.
[0066] Example 1.2 Preparation of CNF-LDH composite film
[0067] The 10 mg / mL MgFe-LDH solution prepared above was ultrasonically treated for 30 minutes, and 1 mL of the above solution was added to 20 g, 40 g, 60 g, and 80 g of CNF solution with a concentration of 0.5 wt.%, respectively, and stirred for 30 minutes to obtain CNF-LDH mixed solutions with a CNF and MgFe-LDH mass ratio of 10:1, 20:1, 30:1, and 40:1, respectively; 100 μL of the mixed solution was added to a 24-well plate containing a climbing sheet and vacuum dried overnight to obtain a CNF-LDH composite film.
[0068] At the same time, 100 μL of a 0.5 wt.% CNF solution was added to a 24-well plate containing a slide and vacuum-dried at 60° C. overnight to obtain a CNF film.
[0069] Example 1.3 Preparation of CNF-LDH aerogel composite material with ordered guided pore structure
[0070] The 10 mg / mL MgFe-LDH solution prepared above was ultrasonically treated for 30 min, and then 1 mL of the solution was added to 20 g, 40 g, 60 g, and 80 g of 0.5 wt.% CNF solution, respectively, and stirred for 30 min to obtain CNF-LDH mixed solutions;
[0071] 30 mL of the above-mentioned CNF-LDH mixed solution and 30 mL of CNF solution were respectively prepared into 50 mL centrifuge tubes, and the bubbles were removed by centrifugation; the centrifuge tube was wrapped with 2 cm thick foam plastic, and the tube mouth was placed upside down on a -198°C copper block immersed in liquid nitrogen for 40 minutes of unidirectional freezing. After freezing, it was freeze-dried at -80°C to obtain CNF-LDH aerogel composite materials with ordered guided pore structures and CNF aerogel materials with guided pore structures, respectively.
[0072] The CNF-LDH mixed solution and CNF solution prepared in this example are as follows Figure 2 As shown in the left figure, Figure 2 The right figure of A is a cross-sectional view of the aerogel material formed after freeze-drying of a CNF-LDH mixture with a CNF and MgFe-LDH mass ratio of 20:1.
[0073] The 20:1 CNF-LDH aerogel composite material was cut into thin slices at high speed along the horizontal or vertical direction. The slices were placed on a silicon wafer and sprayed with a thin layer of gold. The morphology of the scaffold was photographed using a scanning electron microscope (SEM). Figure 2 As shown in Figure B, a neatly arranged microchannel structure with pore sizes ranging from 80 to 225 μm was observed. Energy dispersive spectroscopy (EDS) was also used to directly observe the elemental composition of the CNF-LDH composite. The results showed that the Mg and Fe elements in the MgFe-LDH were evenly distributed throughout the composite.
[0074] Cut the 20:1 CNF-LDH aerogel composite into a scaffold with a diameter of 2 mm x 2 mm x 2 mm (length (length of the guide hole) x width x height). Rehydrate with 6 μL of PBS solution at 4°C overnight and then transplant it into the injured spinal cord. During transplantation, the radial direction of the hole should align with the growth direction of the spinal cord tract at the injured site.
[0075] Example 1.4 Preparation of functionalized CNF-LDH-RS composite scaffold
[0076] The CNF-LDH aerogel composite material with an ordered guide pore structure was cut into a scaffold (mass 6.3-6.7 mg) with a length (guide pore length) × width × height of 2 mm × 20 mm × 20 mm and irradiated with ultraviolet light overnight;
[0077] The scaffold was completely immersed in 600 μL of PBS solution containing 50 μg of sonic hedgehog (SHH) and 15.02 μg of retinoic acid (RA) and rehydrated at 4°C for 24 hours. It was then freeze-dried at -80°C for 24 hours to obtain a functionalized CNF-LDH-RS composite scaffold.
[0078] Cut the composite scaffold into a 2mm x 2mm x 2mm x 2mm long (length of the guide hole) x width x height scaffold, rehydrate it with 6μL PBS solution at 4°C overnight, and then transplant it into the spinal cord injury site. During transplantation, the radial direction of the hole should be aligned with the growth direction of the spinal cord tract at the injury site.
[0079] Example 2: Biocompatibility of CNF-LDH composites
[0080] (1) Recovery and passage of rat brain-derived neural stem cells (NSCs)
[0081] Resuscitate NSCs and transfer the cell suspension to a 15 mL centrifuge tube pre-filled with 2 mL NSC culture medium (DMEM / F12 culture medium containing EGF, bFGF, N2, B27 and 1% double antibody), centrifuge at 1200 rpm for 3 min, discard the supernatant; resuspend in NSC culture medium and transfer to a 10 cm 2 Cells were cultured in Falcon dishes at 37°C and 5% CO2. Half of the culture medium was changed every other day, and cells were passaged every 4 days at a ratio of 1:2. During passage, suspended cell pellets were collected, digested with 2 mL of Accutase at 37°C for 8 min, dispersed into single cells, centrifuged at 1200 rpm for 3 min, and the supernatant discarded. Fresh culture medium was added to the cell pellet, transferred to a new dish, and cultured in a 37°C, 5% CO2 incubator.
[0082] (2) CCK8 assay for cell viability
[0083] The CNF film and CNF-LDH composite film prepared in Example 1.2 were sterilized by UV for 1 h; the cultured NSC cells were inoculated on the film and cultured in growth medium for 48 h; a control group (Control) and a blank control group were also set up: the control group was normal cell culture without the inoculated film; the blank control group was growth medium without cells and the inoculated film; after 48 h of culture, 50 μL of CCK-8 solution was added to 450 μL of culture medium and incubated at 37°C for 3 h; 100 μL of the solution was added to a 96-well plate, and the absorbance value at a wavelength of 450 nm was measured using a microplate reader, and then the cell activity of different groups was calculated.
[0084] Test results see Figure 3 A, Compared with the control group, the cell viability of the CNF film at 48 h was 110.9% ± 9.144%, showing a weak pro-proliferative effect. In comparison, the 10:1 CNF-LDH composite film and the 20:1 CNF-LDH composite film exhibited relatively high cell viability, at 126.4% ± 1.804% and 125.1% ± 12.9%, respectively.
[0085] (3) EdU detection of cell proliferation
[0086] The CNF film and CNF-LDH composite film prepared in Example 1.2 were sterilized by UV for 1 h, and then the cultured NSC cells were seeded on the films and cultured in growth medium for 48 h. A control group (Control) was also set up, which was a normal cell culture without the seeded film. After 48 h of culture, 10 mM 5-ethynyl-2'-deoxyuridine (EdU) was added and incubated for 3 hours to allow it to participate in DNA replication. The cell spheres were then added to a slide coated with poly-l-ornithine (PLO) and cultured in a 37°C, 5% CO2 incubator for 1 h. They were fixed with 4% paraformaldehyde for 15 minutes and 0.5% Triton X-ray diffraction analysis. X-100 permeabilization for 15 minutes; then copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction was performed by incubating cells with azide-containing detection reagent in the dark for 30 minutes to covalently bind EdU through the alkyne moiety; cell nuclei were counterstained with 4',6-diamidino-2-phenylindole (DAPI); and EdU binding to DNA was observed using fluorescence microscopy to analyze cell proliferation. Figure 3 As shown in B and 3C: the diameters of cell spheres grown on CNF films and CNF-LDH composite films with different mass ratios were larger than those in the control group; the average immunofluorescence intensity of EdU-stained cell spheres on the 20:1 CNF-LDH composite film (15.9±1.782) increased by 65% compared with the control group (9.687±1.377).
[0087] Example 3: Regulation of NSC cell fate by CNF-LDH composites and functionalized CNF-LDH-RS composites
[0088] (1) Regulation of NSC cell fate by CNF-LDH composites
[0089] The CNF-LDH aerogel composites with ordered guided pore structures and CNF aerogel materials prepared in Example 1.3 with different mass ratios were cut into scaffolds with the same mass along the transverse direction perpendicular to the pore direction and placed in a 6-well plate, and 0.5 mL of DMEM / F12 medium was rehydrated overnight to obtain CNF-LDH scaffolds and CNF scaffolds; the NSC suspension digested into single cells was injected into the guide hole structure along the pore direction from the cross section of the CNF scaffold and CNF-LDH scaffold; this embodiment also set up a control group, in which NSCs were seeded in a PLO-coated 6-well plate and 2 mL of differentiation medium (DMEM / F12 culture medium containing N2, B27 and 1% double antibody) was added; the well plate was then placed in a 37°C, 5% CO2 cell culture incubator and cultured under spontaneous differentiation conditions for 7 days; 2 mL of differentiation medium was added on the third day; after the 7-day differentiation was completed, the material was washed three times with PBS and the supernatant was removed by centrifugation; TRIzol reagent and magnetic beads were added, and the material was broken and RNA was extracted using a tissue shaker; the expression of NSC lineage differentiation genes was detected by RT-qPCR; Figure 4 As shown: Compared with the control group, the expression of marker genes of neurons (Tuj1 and MAP2) and oligodendrocytes (Olig2) in the CNF scaffold and CNF-LDH composite scaffolds with different mass ratios was significantly increased, while the expression of marker gene of astrocytes (GFAP) was significantly decreased.
[0090] (2) Regulation of NSC cell fate by functionalized CNF-LDH-RS composites
[0091] The CNF-LDH aerogel composite and CNF-aerogel material in Example 1.3 were cut into scaffolds of the same mass along the transverse direction perpendicular to the pore direction and placed in a 6-well plate. A PBS solution containing 1.502 μg RA and 5 μg SHH was added, rehydrated at 4°C for 24 h, and freeze-dried at -80°C for 24 h. Then, 0.5 mL of 10 μg / mL laminin solution was added and coated overnight to obtain functionalized CNF-LDH-RS composite scaffolds or functionalized CNF-RS scaffolds; NSC suspension digested into single cells was injected into the pores along the pore direction from the cross section of the scaffold, and 2 mL of differentiation medium was added; in the control group, NSC was seeded in a laminin-coated 6-well plate and 2 mL of differentiation medium was added; in the RS group, NSC was seeded on a laminin-coated slide and the culture medium was added with RA and SHH in the same amount as the scaffold;
[0092] The well plate was then placed in a 37°C, 5% CO2 cell culture incubator and cultured under spontaneous differentiation conditions for 7 days. On the third day, 2 mL of differentiation medium was added until the end of differentiation. After 7 days of differentiation, the material was washed three times with PBS, the supernatant was removed by centrifugation, TRIzol reagent and magnetic beads were added, and the material was broken using a tissue shaker and RNA was extracted for RT-qPCR analysis. Figure 5 shown.
[0093] The results showed that compared with the control group, the expression of neuronal (Tuj1 and MAP2) and oligodendrocyte (Olig2) marker genes in the CNF-RS scaffold group and the functionalized CNF-LDH-RS composite scaffold groups with different mass ratios was significantly increased, while the expression of astrocyte (GFAP) marker gene was significantly decreased. Among them, the 20:1 functionalized CNF-LDH-RS composite scaffold group had the most significant effect on promoting neuronal differentiation.
[0094] Example 4: Functionalized CNF-LDH-RS composite scaffold promotes motor function recovery and neural circuit connectivity in spinal cord injured mice
[0095] 6-8 week old SPF grade C57BL / 6 mice were purchased (Jiesjie Experimental Animal Co., Ltd.) and divided into sham operation group, SCI group (spinal cord injury group), RS group, CNF-LDH group and CNF-LDH-RS group, with 10 mice in each group.
[0096] (1) Construction of a mouse spinal cord aspiration injury model:
[0097] Place a C57BL / 6 mouse in an anesthesia box, turn on the anesthetic gas knob, and inhale anesthesia with 1.5% isoflurane (Shenzhen Ruiwode Life Science Co., Ltd.) mixed with air, and adjust the anesthetic dose to 0.2L / min. When the mouse's limbs are inactive, the pain reflex disappears completely, and the breathing is slow and steady, it indicates that the mouse has entered an anesthetized state. Immediately remove the mouse and shave the hair and prepare the skin with a shaver. Fix it on a standard rodent brain stereotaxic instrument (Shenzhen Ruiwode Life Science Co., Ltd.), with the tail hanging naturally, and straighten and fix it with tape so that the mouse spine is in a straight line. First clean the back with an alcohol cotton swab, then disinfect it 3 times with iodine cotton swabs, and then deiodine it 3 times with 75% alcohol. Adjust the field of view and focus of the stereoscopic visual microscope until the surgical field is clear. Locate the T10 spinous process and use a sharp knife surgical blade to make a midline incision on the back, about 2 cm long, with this as the center. Use toothed forceps to separate the mouse's back fat, fascia and muscle tissue layer by layer until the T9-T11 vertebral plates are completely exposed. The supraspinal and interspinous ligaments were removed using ophthalmic microscissors. The pedicles of T10 were also cut with ophthalmic microscissors, and the T10 lamina was carefully removed. The spinous processes of T9 and T11 were clamped with mosquito clamps and pulled bilaterally to stabilize the spinal cord. A 2 mm section of spinal cord tissue was removed using a vacuum pump, with the posterior median vessels at the center, from the corresponding region of T10 as the injury site to establish a spinal cord aspiration injury model in mice.
[0098] In the sham operation group, only the lamina was removed without spinal cord injury.
[0099] In the scaffold transplantation group, the CNF-LDH composite scaffold described in Example 1.3 (CNF-LDH group) or the functionalized CNF-LDH-RS composite scaffold described in Example 1.4 (CNF-LDH-RS group) was immediately filled after the spinal cord tissue was removed.
[0100] In the RS group, 6 μL of PBS solution containing 1.502 μg RA and 5 μg SHH was injected in situ at the injury site.
[0101] After complete hemostasis at the injury site, the fascia and skin covering the back of the muscle were sutured layer by layer. The wound was cleaned and disinfected with alcohol. The mouse was placed on a constant temperature plate for 2 hours. Once fully awake, it was returned to its cage. Artificial urination was performed daily postoperatively until bladder function returned to normal. Antibiotics and analgesics were also administered.
[0102] (2) Evaluation of motor function recovery in animals with spinal cord injury
[0103] The motor function assessment (BMS) and motor evoked potential (MEP) experiments were used to further evaluate the motor function recovery of the spinal cord injured mice in different groups. 1-8 weeks after surgery, the mice were placed in an open field for BMS scoring. The BMS scoring observation period for mice was 4 minutes. Video recordings of the left and right foot movement performance of the mice were compared with the BMS system scoring criteria and scored separately. The results are as follows: Figure 6A and 6B shown.
[0104] The motor evoked potential experiment was conducted 8 weeks after surgery, with three mice randomly selected from each group. The anesthetized mice were placed on a stereotaxic apparatus, their hair and muscles removed, and a 3 mm long and 5 mm wide opening drilled with a cranial drill. The skull was removed to expose the meninges of the hindlimb sensorimotor cortex. Electrodes were attached to the meninges to provide 1.5 mA stimulation, and bipolar disc electrodes were used to collect and record MEP signals from the sciatic nerve. The MEP waveform amplitude and latency of each group of animals were quantitatively analyzed using Matlab. The results are shown in the figure below. Figure 6C and 6D shown.
[0105] The results showed that the BMS score of the RS group was higher than that of the SCI group, but there was no significant difference between them. This shows that after in situ injection of RA and SHH factors immediately after SCI surgery, the motor behavior of SCI mice can be improved, but this recovery effect is limited and cannot significantly improve the BMS score and histological manifestations. Compared with the RS group and CNF-LDH group, the functionalized CNF-LDH-RS group had significantly improved hindlimb motor function of mice, indicating that the presence of the scaffold improved the utilization of factors and avoided excessive loss caused by cerebrospinal fluid. In the SCI group, mice were observed to have slight ankle joint movement ability. In the CNF-LDH group and the functionalized CNF-LDH-RS group, most of the mice could complete a certain degree of hindlimb movement. The above results prove that the neural circuits in the injured area were reshaped after scaffold transplantation, and were effectively integrated with the ascending and descending neural circuits to a certain extent, promoting nerve conduction and guiding the completion of hindlimb movement.
[0106] (3) Evaluation of neuronal regeneration and neural circuit reconstruction in the spinal cord injury area
[0107] To evaluate whether the histomorphological changes at the injured area of mice are consistent with the recovery of motor function, this example performed immunofluorescence staining of the early neuron marker protein Tuj1 on the injured area 3 and 6 weeks after injury; and performed immunofluorescence staining of the mature neuron marker protein MAP2 and the astrocyte marker protein GFAP on the injured area 8 weeks after injury, and evaluated the reconstruction of the neural circuit, as follows:
[0108] Three weeks and six weeks after scaffold transplantation, three mice were randomly selected from each group and subjected to cardiac perfusion. Spinal cord tissue was taken, embedded and sliced, and immunofluorescence staining was performed. Eight weeks after scaffold transplantation, three mice were randomly selected from each group. The anesthetized mice were placed on a stereotaxic apparatus, the hair and muscles were removed, a small hole with a diameter of 0.8 mm was drilled with a cranial drill, and the skull was removed to expose the hindlimb sensory motor cortex area M1. The needle tip of the microinjector was positioned at the center of the small hole made by the cranial drill, and 250 nL of HSV-129-G4 was injected 1.4-1.2 mm below the surface of the pia mater at a controlled rate of 25 nL / min. After 48 hours of treatment, the mice were cardiac perfused, spinal cord tissue was taken, embedded and sliced, and immunofluorescence staining was performed, as shown in FIG. Figure 7 and 8 .
[0109] from Figure 7 As can be seen in A and 7B, more Tuj1-positive neurons were found in the injured area 3 weeks after implantation of the functionalized CNF-LDH-RS composite scaffold, and axon regeneration along the microchannels of the scaffold increased. Figure 7 As can be seen from CE, Tuj1-positive neurons were found to be widely present in the 2mm injury area in the injury area 6 weeks after injury, and some neurons reached the distal end of the injury and integrated into the host spinal cord tissue. The total amount of axon regeneration across the lesion boundary in the functionalized CNF-LDH-RS composite scaffold group was more than 13 times that of the SCI group, and the average axon length reached 196.5μm, which was 2.26 times that of 3 weeks after transplantation. Even the longest axon length around the central canal in the center of the injury area reached 419μm. Figure 8 As can be seen, the number of MAP2-positive cells in the injured area of the SCI and RS groups was significantly less than that in the CNF-LDH and functionalized CNF-LDH-RS groups 8 weeks after spinal cord injury. In the functionalized CNF-LDH-RS group, MAP2-positive cells penetrated the lesion center along the scaffold pores.
[0110] from Figure 9 As can be seen in the functionalized CNF-LDH-RS group, a high proportion of GFP-labeled neurons co-localized with MAP2-positive neurons was observed. The SCI group mice showed that only a small number of GFP-labeled neurons could cross the injury area. In both the CNF-LDH and functionalized CNF-LDH-RS groups, GFP-labeled axons regenerated within the injury area and passed through the injury area to the distal end, suggesting that descending motor function-related axons may have connected with regenerated spinal cord axons, which was more obvious in the functionalized CNF-LDH-RS group.
[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a cellulose nanofiber-layered double hydroxide composite material, characterized in that: The following steps are involved: The layered double hydroxide and the cellulose nanofibers are uniformly mixed in a solution, and the cellulose nanofiber-layered double hydroxide composite material is obtained through ① drying or ② unidirectional freezing.
2. The preparation method according to claim 1, characterized in that: The layered double hydroxide is magnesium-iron layered double hydroxide; Preferably, the mass ratio of the cellulose nanofibers to the layered double hydroxide is 10-40:
1.
3. The preparation method according to claim 2, characterized in that: The preparation method of the magnesium-iron layered double hydroxide comprises the following steps: S1. Add the mixed solution of magnesium nitrate and ferric nitrate to the NaOH solution and stir at 25-60°C for 30-60 minutes; S2. The product of step S1 is subjected to a hydrothermal reaction at 80 to 120° C. for 14 to 18 hours to obtain a magnesium / iron layered double hydroxide; Preferably, the molar ratio of magnesium to iron in the magnesium nitrate and ferric nitrate is (0.1-5):1; Preferably, after the mixed solution of magnesium nitrate and ferric nitrate is added to the NaOH solution, the final molar concentration ratio of magnesium nitrate to sodium hydroxide is (0.375-1.2):1; Preferably, the solvent of the mixed solution of magnesium nitrate and ferric nitrate is CO2-free deionized water; Preferably, the solvent of the NaOH solution is CO2-free deionized water; Preferably, the stirring reaction in step S1 is carried out under continuous nitrogen flow.
4. The preparation method according to claim 1, characterized in that: The drying is vacuum drying; Preferably, the drying temperature is 40 to 80°C; Preferably, the one-way freezing is to introduce the uniformly mixed solution into a mold having one side made of metal and the other side made of non-thermal conductive material, and perform one-way freezing; Preferably, the temperature of the one-way freezing is -80 to -196°C; Preferably, the thermal conductivity of the metal is ≥400 W / (m*K); Preferably, the one-way freezing time is 40 to 60 minutes; Preferably, the uniformly mixed solution is subjected to a centrifugal operation to remove air bubbles before being unidirectionally frozen; Preferably, the one-way freezing further comprises freeze drying; Preferably, the freeze-drying temperature is -80 to 85°C.
5. The cellulose nanofiber-layered double hydroxide composite material obtained by the preparation method according to any one of claims 1 to 4.
6. A method for preparing a functionalized cellulose nanofiber-layered double hydroxide composite material, characterized in that: The following steps are involved: The cellulose nanofiber-layered double hydroxide composite material according to claim 5 is treated under ultraviolet light, immersed in a mixed solution containing sonic hedgehog and vitamin A acid, and freeze-dried to obtain the functionalized cellulose nanofiber-layered double hydroxide composite material.
7. The preparation method according to claim 6, characterized in that: The ultraviolet treatment time is 16 to 24 hours; Preferably, the ratio of the mass of the cellulose nanofiber-layered double hydroxide composite material to the total mass of the sonic hedgehog and vitamin A acid is 10 to 1000:1; Preferably, the mass ratio of vitamin A acid to sonic hedgehog factor is 1 to 20:10; Preferably, the solvent in the mixed solution containing sonic hedgehog and retinoic acid is PBS buffer solution; Preferably, the freeze-drying temperature is -80 to 85°C.
8. The functionalized cellulose nanofiber-layered double hydroxide composite material obtained by the preparation method according to any one of claims 6 to 7.
9. Use of the preparation method according to claim 1, the cellulose nanofiber-layered double hydroxide composite material according to claim 5, the preparation method according to claim 6 or the functionalized cellulose nanofiber-layered double hydroxide composite material according to claim 8 in preparing a biological scaffold.
10. The use according to claim 9, characterized in that: The preparation of the bioscaffold comprises rehydrating the cellulose nanofiber-layered double hydroxide composite material or the functionalized cellulose nanofiber-layered double hydroxide composite material; Preferably, the temperature of the rehydration operation is 4-8°C; Preferably, the rehydration operation time is 1 to 12 hours.